If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 3) + -4(x + 1) = 0 Reorder the terms: 5(3 + x) + -4(x + 1) = 0 (3 * 5 + x * 5) + -4(x + 1) = 0 (15 + 5x) + -4(x + 1) = 0 Reorder the terms: 15 + 5x + -4(1 + x) = 0 15 + 5x + (1 * -4 + x * -4) = 0 15 + 5x + (-4 + -4x) = 0 Reorder the terms: 15 + -4 + 5x + -4x = 0 Combine like terms: 15 + -4 = 11 11 + 5x + -4x = 0 Combine like terms: 5x + -4x = 1x 11 + 1x = 0 Solving 11 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 1x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + 1x = 0 + -11 1x = 0 + -11 Combine like terms: 0 + -11 = -11 1x = -11 Divide each side by '1'. x = -11 Simplifying x = -11
| x^2+4x+1-x^2+17=0 | | ln(3t)=1.9 | | 3(1-3x)=14-8x | | 13+9n=22 | | y^4-16y=0 | | 6-(-27)/2(-9) | | x^2+12x+4y-12=0 | | 11n+2=24 | | 13y+5.2=2-5y | | -10+7x=14+5x | | 3(4x-3)=7 | | 36=2/3u | | -5=3n-8 | | 8-2n=3n+13 | | 11n+6=24 | | -12+5x=-9 | | X/4-X/8=-7/8 | | 4n-4=8+7n | | -n-1/2=10 | | 0=18x+1 | | 2(4x-15)=3(x-15) | | 2x+10=5+3x | | 7a+16-3a=-44 | | 9+10a=10 | | (x-2)=3(x-3) | | (X)=2(1+3) | | 2(4x-15)=3(x+15) | | 3+3p=6 | | 4a+12=7 | | 4(x-9)=x-15 | | 4(y-8)=8 | | m/3-6 |